Perceived Information Technology in The Operational Region of PT Kereta Api Indonesia - Yulianeu, Aneu; Sukmana, Wawan; Budiman, H. Asep (Universitas Brawijaya, Indonesia, 2016)
To get the benefit of technology of information optimally and produce the result that we hope, furthermore it needs leadership that could stimulate the employers as users of technology reformation to increase the level of acceptance that integrated with educational degree of employers a moderator into the influence of transactional leadership, transformational in using perceived information technology. This research use three standardized questionnaire, Multifactor Leadership Questionnaire, questionnaire of educational degree to the e r foyers and technology acceptance model. This research has been done at PT. KeretaApi Indonesia operational region II Bandung. The number of questionnaire that has been distributed was 65 (sixty five), they were spread at 5 departments at PT. K.A.I operational region II Bandung. The result from analysis of hierarchy regression found out that the educational degree moderate the influence of transactional leadership and transformational towards technology information of perception. The result of this research found that only transformational leadership that has significant influence to the use of technology of perception information.